phenomenological perspective of physical activity and sports at the Dean of Sciences UCLA veterinarians (Revista Electrónica REDINE, 2019)
The present study was based on a phenomenological investigation of physical and sports activity in the Deanery of Veterinary Sciences of the Centroccidental University "Lisandro Alvarado, framed in the qualitative approach in the interpretive paradigm. At the same time, it relied on field research, where the systematic analysis of problems in reality is sought, with the purpose of either describing and interpreting them, explaining their causes and effects; of interpretative character. Informal interviews were applied to social actors made up of two teachers, two administrative staff and one student, and the information provided by each of the subjects studied was described, being ordered by categories that were interpreted by the author of the research through of the triangulation of the information coming to the following considerations, that the teaching, administrative and student personnel of the Dean of Veterinary Sciences of the UCLA does not practice in a regular and systematic way the physical activity within the habits for the development and maintenance of their health , being extremely beneficial in the prevention of diseases and improvements in the quality of life. Also as a means to forge the character, discipline, decision making and compliance with the rules, benefiting the development in all areas of daily life.